Present scenario of renewable energy sources in Mymensingh and Pabna districts - Sultana, R; Rahman, MA; Yeasmin, M; Auyon, ST; Islam, MA (Progressive Agriculture, 2018)
The study was carried out to investigate the present scenario of renewable energy sources in Pabna and Mymensingh districts. Data were collected by interviewing 120 randomly selected respondents in each study areas during the period of September 2016 to July 2017. It was observed that available sources of renewable energy were mainly solar, biogas and biomass in both districts. Data were collected based on various independent and dependent variables. The findings revealed that 53.3% respondents in Pabna and 63.3% respondents in Mymensingh showed positive response to renewable energy sources. It was also observed that 38.3% respondents of Pabna had medium and 41.7% respondents of Mymensingh had high familiarity with renewable energy sources. The majority of the respondents commented that biomass energy in Pabna and biogas energy in Mymensingh was the most cost effective sources and the major contribution to energy comes from mainly biogas in Pabna and solar energy in Mymensingh. Besides, a questionnaire survey was done in different GOs and NGOs which involving for creating public awareness and community level sources maintenance in both districts. The most effective strategy of the organization is education and capacity building program in Pabna and in Mymensingh it was renewable energy markets, financing mechanism. The most effective awareness program was found campaigning in Pabna and in Mymensingh it was direct consultation. Survey result showed that 50% organization provided medium amount of loan (5000-8000) in Pabna and in Mymensingh it was 65%. The most effective training program was found customer training in Pabna district and in case of Mymensingh district it was customer motivating training. The majority of the respondents’ percept that government should provide more subsidies to make renewable sources more affordable in case of both study area. The most of the respondents’ percept that saving money was most important for using renewable energy sources in Pabna and in Mymensingh it was availability of renewable energy sources. Therefore, the GO and the NGO should work hand in hand to emphasize more on renewable energy source to produce electricity to solve their power crisis problem. Progressive Agriculture 29 (2): 71-81, 2018